Waste polymer blended with copolymer polypropylene to enhance mechanical properties using injection moulding - S., N. Afiqah; M. Rus, Anika Zafiah; Syah, A. Shahrizan; M. J., Farhana Hazwanee; M., Noraini; I., S. Aida (Science Publishing Corporation, 2018)
This study was constructed to examine the tensile properties and the microstructure of wood-plastic composites (WPCs) before and after being subjected to UV irradiation. The pellet of the wood polymer composites consists of waste polypropylene as the matrix and rice-husk flour as the reinforcing filler. They were mixed blended with virgin copolymer polypropylene through injection moulding and were UV irradiated from 1000 hours to 3000 hours to study the effect of weathering on the tensile properties of the WPCs. The microstruc-tures of the fractured surface of the specimens were examined under Scanning Electron Microscope (SEM). The tensile properties of the composites decreased with the increase of UV irradiation due to photo degradation. Adding copolymer polypropylene by 10-30 wt% in the composition helps improve the tensile properties of the WPCs.